Clinical and genetic aspects in the Ehlers Danlos syndrome - Elena Silvia Shelby; Madalina Cristina Leanca; Serban Hamei; Liliana Padure; Andrada Mirea (Amaltea Medical Publishing House, 2020)
Introduction. Ehlers Danlos syndrome is a group of hereditary diseases of the connective tissue with a combined prevalence of 1 in 5,000 cases which have in common articular hyperlaxity and skin abnormalities. In some types, rapid diagnosis can mean saving the life of the patient. Case presentation. We will present the case of a two year old girl which was brought for genetic consult with the suspicion of Ehlers Danlos syndrome. The patient had joint and skin hyperextensibility, velvety skin with a tendency of bruising, congenital hip luxation with a failed surgical intervention, talus varus and severe motor development retardation. Genetic testing revealed the substitution c.1780C>T, p.(Arg594*) in the COL5A1 gene which leads to the apparition of a premature stop codon, the mutation being class 2 (potentially pathogenic). Conclusions. Up until now, this variant has been reported in the literature in only two patients, ours being the third. All three cases correspond to the classic type Ehlers Danlos syndrome.